Igor Rostislavovich Shafarevich (03.06.1923 -- 19.02.2017) - Drozd, Yu.; Kirichenko, V.; Petravhuk, A.; Petrychkvych, V.; Shapochka, I.; Zabavskiy, B.; Zhuchok, A.; Varbanets, P. (Algebra and Discrete Mathematics, 2017)
The great Russian mathematician Igor Rostislavovich Shafarevich died on February 19, 2017. This news grieved the whole mathematical society, since his name was inseparably linked to so many outstanding achievements and ideas of the modern mathematics, especially number theory and algebraic geometry.